(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
For many years, the international community has been involved in establishing practical courses on information literacy in various countries all over the world, aiming to set the methodological and cognitive foundations that will help the receivers of media content to interact with the media in a critical and constructive manner. Considering that the audience is the focus of information literacy, it is necessary to understand it in order to have an effective role in pushing the media towards a more quality media production industry. Over nearly a century, the audience has been considered by the operations of audio-visual media audience measurements as just a "number" emptied of its cognitive competencies, value acquisitions and creative capabilities. The global system for media audience measurement also contributed to creating competition among media institutions that led to audience segmentation and dispersion among several media platforms, as it became an isolated audience. And the audience, according to the logic of the rent economy that characterizes the media field, is a natural capital with which the media achieves wealth and economic sustainability in the media market. The paths of information literacy cannot remove the audience from the socio-economic context that characterizes the global media environment, as it must deal with it not according to its socio-cultural identifiers, but rather on the grounds that it is an investor in the media sector who pumps his money, devotes his time and makes an effort to follow the media and its updates. From this point of view, the orientation towards institutionalizing the media audience becomes something urgent, where audience institutions are a major format in the information literacy system along with media institutions and information literacy institutions. These main patterns agree on the basic elements that make up the system, which are modification mechanisms that are mainly summarized in the critical tools of knowledge, methodologies, techniques and others to evaluate the media morally and push it towards the production of a more quality media content. The audience then is a positive partner with all its suggestions and opinions in the media production process and is not a passive consumer of the media, which is the image that should present the interactive relationship between the media and the audience after establishing a balanced education system on the media. While the global system for media audience measurement has contributed for decades to valuing the media and marginalizing the audience, the establishment of solid foundations for a global system for information literacy would limit the dominance of a capitalist socio-economic model that has dominated the activity of the media sector all over the world and contributed to content trading media and emptied it of its developmental dimensions for human being and society. The scientific methodological systemic approach helps to think deeply about the details of a global system of information literacy that is balanced in terms of the internal and external relations of the various components that constitute it. And it reveals to us that systemic imbalance on which the prevailing experiences in the field of information literacy are based, as relying on building institutions specialized in information literacy is not enough to push towards the quality media industry, but rather it creates an amateur alternative media, in the medium or long term. The goal at that time should be based on equipping the media audience, and not just young people or youth category, with the mechanisms of directing the media towards producing good media content and the direction of its urgent and immediate modification. The systemic method is also used to search for the future of the information literacy system and to reveal its objectives and orientations as well. The field of media and communication sciences, in cooperation with social sciences and economic sciences can work according to a critical approach to the audience to think again of the media audience and unify concepts about it, in line with the socio-economic context of the media sector.